Le Petit Prince –Teenage Suicide - Dammann †, Gerhard; Polishchuk, Вікторія (Psychosomatic Medicine and General Practice, 2020)
Suicide and suicidal ideation among adolescents and young adults are some of the most burdensome experiences for families, relatives, and therapists. In the phase of life, which should be characterized by awakening, cheerfulness and vitality, a group of adolescents appears, burdened with serious suicidal thoughts. This paper will investigate this phenomenon from a clinical point of view, and also show that there are important links between developmental objectives, critical aspects of adolescence and suicidality. A psychodynamic approach is usually used in research on this phenomenon, although there are also several cognitive-behavioral approaches to the phenomenon of suicidality in adolescents.